Measurement of Wear in Orthopedic Prosthesis - Sagbas, B.; Durakbasa, M. Numan (POLISH ACAD SCIENCES INST PHYSICS, 2012)
Wear in orthopedic prosthesis has been the main limiting factor of total joint replacement's service life. Wear analysis of total joint replacements is essential for determining failure mechanism, prediction of wear and longevity of implants. So it would be possible to improve design, material and manufacturing quality and service life of these devices. Radiographic, gravimetric, volumetric and optical techniques are current methods for measuring of wear in retrieved implants. Gravimetric method is the standardized method for quantifying wear volumes of total joint prosthesis. Although this method is effective for determining experimental wear volume in simulated conditions, it is not suitable for assessing the clinically retrieved prosthesis for which there is no pre-wear data available. Each of the wear measuring methods has advantages and limitations. Researches have been going on for developing effective methods. In this paper the techniques that are currently used for evaluating wear of orthopedic prosthesis like gravimetry, coordinate measuring machine, micro computed tomography, and digital photogrammetry are explained. The literature works and new trends in metrological assessment of wear are reviewed.
Keywords: POLYETHYLENE; VALIDATION; METROLOGY; UHMWPE; Physics